A narrative review on the impact of applied artificial intelligence tools on higher secondary students - Mohamud, Yasmin Abdullahi; Ma’rof, Aini Azeqa; Mohamed, Abdullahi Mohamud; Hossain Uzir, Md Uzir (Human Resource Management Academic Research Society, 2023)
The education sector is witnessing a surge in the use of applied artificial intelligence (AAI) tools/devices, which offer potential advantages such as personalized learning experiences, increased student engagement, and improved academic performance. However, concerns have been raised about the potential negative impacts of these technologies, including overreliance on the Applied Artificial Intelligence (AAI) tools and devices, decreased social interaction, and less critical thinking skills. Through a comprehensive review of the literature, this review emphasized the benefits and drawbacks of using AAI tools/devices in higher secondary education, providing a comparative view of their effectiveness. In addition, the paper considers the perspectives of educators, students, and parents, and will draw on examples of successful implementation of AAI technology in education. Moreover, the review provides a balanced and informed view of the merits and demerits of using AAI tools/devices for higher secondary students, offering insights into their potential impact on education outcomes and highlighting the need for responsible and ethical deployment.